Dual roles of 3-aminopropyltriethoxysilane in preparing molecularly imprinted silica particles for specific recognition of target molecules. Issue 34 (27th May 2020) - Wang, Fenying; Ling, Baoping; Li, Qianjin; Abouhany, Rahma
Abstract : A novel strategy was developed for preparing highly selective molecularly imprinted polymers using 3-aminopropyltriethoxysilane as both a functional monomer and catalyst. Abstract : 3-Aminopropyltriethoxysilane (APTES) is a silane widely used to supply amino groups for further modifications on various materials, but it is less studied as a catalyst to catalyze sol–gel silica polymerization. Here, by using APTES as the catalyst instead of the conventional basic catalysts, a novel strategy was developed to prepare silica-based molecularly imprinted polymers (MIPs). Meanwhile, APTES was employed as the functional monomer to create imprinted nanocavities for specific recognition of target molecules. The as-synthesized MIP exhibited ultra-high recognition capability due to the elimination of the detrimental effect on the imprinting performance caused by the additional catalysts. The preparation process, specificity, pH effect, binding capacity and affinity of the MIP were studied in detail. The MIP microparticles could be packed into a solid phase extraction column for removing the target molecule in water efficiently, and the molecule could easily be enriched by 40 times. The interaction of the functional monomer and template was studied by the calculation method, giving a more clear understanding of the recognition behaviours of the imprinted polymers. The strategy could be extended not only to prepare highly specific MIPs for other small phosphoric molecules, but also for biomolecules e.g. phosphorylated peptides or proteins.